The Relationship Between Nonqualified Allopathic Medical Practitioners and Their Patients - Abeysinghe, Dilrukshi (My University, 2008)
Objective: According to unpublished data issued by the Sri Lankan health authorities, approximately 40,000 individuals who are not medically qualified are engaged in allopathic medical practice in many parts of the country. Despite the existence of restrictive legislation for the regulation of allopathic medical practice, distribution of allopathic drugs, and their prescription, the presence of nonqualified allopathic medical practitioners (NQAMPs) shows that such legislation is not wholly effective. This paper does not look at the range of factors that creates the environment for the NQAMPs to continue practicing medicine. The main objective of this paper is to present a sociological analysis of the practitioner-patient relationship mainly from the viewpoint of patients who have consulted NQAMPs. Materials and methods: Ten NQAMPs who practice allopathic medicine in the Ratnapura district and 350 patients who sought treatment from them were selected for the study. The in-depth interview method and observation method were used to collect qualitative information. Results: A significant feature among those who visited NQAMPs for treatment was that 94% of employed patients were earning their living on a day-to-day basis. Of these, 88% had no schooling at all or had only a primary level education. Also among the patients who consulted NQAMPs was a small group (0.3% of 350) of those engaged in professions such as teaching and clerical work who earned regular monthly salaries and a few (0.5%) who had tertiary and higher education. This paper reveals the success of the NQAMPs in establishing a close relationship with these patients as compared to the allopathic medical practitioners in the formal healthcare sector.
Keywords: The Relationship Between Nonqualified Allopathic Medical Practitioners and Their Patients